2002
DOI: 10.1163/20021975-99990246
|View full text |Cite
|
Sign up to set email alerts
|

Egg Production Strategies of the Tropical Hermit Crab Paguristes Tortugae from Brazil

Abstract: A B S T R A C TThe aim of the present study was to characterize the total and seasonal fecundity of the hermit crab Paguristes tortugae as well as the influence of shell type on fecundity using the morphometric relationship. Ovigerous females were collected monthly from January to December, 1998, in the infralittoral region of Anchieta Island. Samplings were performed using SCUBA. The hermit crabs and the gastropod shells were measured. Hermit wet weight and shell dry weight were recorded. For the fecundity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 15 publications
(30 reference statements)
5
13
0
1
Order By: Relevance
“…(2004; p. 2341) after a study on the gonadal development of L. loxochelis proposed that ‘this hermit crab species has the capacity to copulate and deposit another brood soon after the release of the larvae, thus intensifying the reproductive effort’. In the present study population, ovigerous females of different sizes were observed with embryos at all developmental stages, suggesting that embryonic development is a continuous process (Mantelatto et al . 2002), in accordance with their continuous reproductive activity (Martinelli et al .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…(2004; p. 2341) after a study on the gonadal development of L. loxochelis proposed that ‘this hermit crab species has the capacity to copulate and deposit another brood soon after the release of the larvae, thus intensifying the reproductive effort’. In the present study population, ovigerous females of different sizes were observed with embryos at all developmental stages, suggesting that embryonic development is a continuous process (Mantelatto et al . 2002), in accordance with their continuous reproductive activity (Martinelli et al .…”
Section: Discussionmentioning
confidence: 57%
“…Loxopagurus loxochelis produces more eggs than Paguristes Dana 1851 genera (Negreiros‐Fransozo et al . 1992; Garcia and Mantelatto 2001; Mantelatto et al . 2002; Williams 2002), which, for instance, produce larger eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the hypothesis that best adjusts to the use of shells with less internal infestation by ovigerous females is related to the physiological need of the species to maximize reproductive success. Mantelatto et al (2002), studying Paguristes tortugae Schmitt, 1933, found a positive correlation between fecundity and the internal volume of the shell, suggesting that the larger the volume, the greater the fecundity of the female. In the present study, this might explain the low prevalence of internal epibionts in the shells occupied by ovigerous females, because internal epibionts limit the space available for oviposition and development of fertilized eggs, and some polychaete epibionts of the genus Polydora use hermit crab eggs as food (Williams, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…According to Hazlett et al (2005) females of Clibanarius vittatus (Bosc, 1802) that occupied heavier shells -larger than their ideal size -tended not to be ovigerous, whereas ovigerous females were most commonly found in adequate shells. When analyzing egg production strategies in Paguristes tortugae (Schmitt, 1933), Mantelatto et al (2002) reported that the occupation of some shells provided an increase in fecundity. The same was shown for Loxopagurus loxochelis (Moreira, 1901) by Torati and Mantelatto (2008), who also showed that this increase in fecundity takes place particularly when the shell is lighter.…”
Section: Discussionmentioning
confidence: 99%